Pengaruh Ujrah dan Dana Tabarru'Terhadap Pendapatan Investasi Pada Perusahaan Asuransi Jiwa Syariah di Indonesia Periode 2016-2021 - Mei Habibah Dalimunthe; Maryam Batubara; Wahyu Syarvina (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This study aims to determine the effect of ujrah and tabarru' funds on investment income in Islamic life insurance companies in Indonesia for the 2016-2021 period, the effect of Ujrah on investment income in Islamic life insurance companies in Indonesia for the 2016-2021 period, the effect of Tabarru' funds on investment income in Islamic life insurance companies in Indonesia for the 2016-2021 period, do Ujrah and Tabarru' Funds affect investment income in Islamic life insurance companies in Indonesia for the 2016-2021 period, and how much influence do Ujrah and Tabarru' Funds have on investment income in life insurance companies sharia in Indonesia for the 2016-2021 period. The method used in this study is quantitative, by taking financial data samples from 6 companies in the 2016-2021 period, namely PT Asuransi Jiwa Manulife Indonesia, PT Prudential Life Assurance, PT Asuransi Takaful Keluarga, PT Asuransi Jiwa Sinarmas MSIG, PT Asuransi Jiwa Central Asia Raya. , PT. BNI Life Insurance Syariah. Based on the results of the calculation of the simultaneous regression coefficient test (Test f) it can be concluded that the variable Ujrah (X1) and Tabarru' Funds (X2) have an effect on investment income (Y), namely Fcount 159.129 > Ftable 3.28, with a significance value of 0.000 <0 ,05. And test the coefficient of determination (R2) of 0.900. This shows that the Ujrah and Tabarru Fund variables have an effect on investment income, namely 90.0%, while the remaining 10.0% is influenced by other variables that are not included and not examined in this study.